A Plasmonic Infrared Multiple-Channel Filter Based on Gold Composite Nanocavities Metasurface - Zhang, Jialin (Nanomaterials (Basel), 2021)
A plasmonic near-infrared multiple-channel filter is numerically and experimentally investigated based on a gold periodic composite nanocavities metasurface. By the interference among different excited plasmonic modes on the metasurface, the multipeak extraordinary optical transmission (EOT) phenomenon is induced and utilized to realize multiple-channel filtering. Investigated from the simulated transmission spectrum of the metasurface, the positions and intensity of transmission peaks are tuned by the geometrical parameters of the metasurface and environmental refractive index. The fabricated metasurface approached transmission peaks at 1128 nm, 1245 nm, and 1362 nm, functioning as a three-passbands filter. With advantages of brief single-layer fabrication and multi-frequency selectivity, the proposed plasmonic filter has potential possibilities of integration in nano-photonic switching, detecting and biological sensing systems.